VD_FINDINFO HC / 2009 / 453 vom 22. Dezember 2009 - VD Tribunal cantonal (2009)
MESURE DE CONTRAINTEDROIT DES ÉTRANGERS | 76 al. 1 let. b ch. 3 LEtr, 76 al. 1 let. b ch. 4 LEtr, 80 al. 1 LEtr, 80 al. 6 LEtr, 30 LVLEtr, 31 LVLEtr